Colibactin Contributes to the Hypervirulence of pks+ K1 CC23 Klebsiella pneumoniae in Mouse Meningitis Infections - Lu, Min-Chi; Chen, Ying-Tsong; Chiang, Ming-Ko; Wang, Yao-Chen; Hsiao, Pei-Yi; Huang, Yi-Jhen; Lin, Ching-Ting; Cheng, Ching-Chang; Liang, Chih-Lung; Lai, Yi-Chyi (Frontiers in Cellular and Infection Microbiology, 2017)
Klebsiella pneumoniae is the most common pathogen of community-acquired meningitis in Taiwan. However, the lack of a physiologically relevant meningitis model for K. pneumoniae has impeded research into its pathogenesis mechanism. Based on phylogenetic analyses of a core genome MLST scheme, the hypervirulent K1 K. pneumoniae strains, which are etiologically implicated in adult meningitis, mostly belong to a single clonal complex, CC23. Some K1 CC23 K. pneumoniae strains carry a gene cluster responsible for colibactin production. Colibactin is a small genotoxic molecule biosynthesized by an NRPS-PKS complex, which is encoded by genes located on the pks island. Compared to other hypervirulent K. pneumoniae which primarily infect the liver, the colibactin-producing (pks+) K1 CC23 strains had significant tropism towards the brain of BALB/c mice. We aimed in this study to develop a physiologically relevant meningitis model with the use of pks+ K1 CC23 K. pneumoniae. Acute meningitis was successfully induced in adult BALB/c male mice through orogastric, intranasal, and intravenous inoculation of pks+ K1 CC23 K. pneumoniae. Besides the typical symptoms of bacterial meningitis, severe DNA damages and caspase 3-independent cell death were elicited by the colibactin-producing K1 CC23 K. pneumoniae strain. The deletion of clbA, which abolished the production of colibactin, substantially hindered K. pneumoniae hypervirulence in the key pathogenic steps towards the development of meningitis. Our findings collectively demonstrated that colibactin was necessary but not sufficient for the meningeal tropism of pks+ K1 CC23 K. pneumoniae, and the mouse model established in this study can be applied to identify other virulence factors participating in the development of this life-threatening disease.